Endoscopic Proximal Hamstring Repair Using a Modified Whipstitch: A Technical Note - Eric J. Cotter MD; Omair Kazi MS; Michael J. Vogel BS; Shane J. Nho MD, MS (Video Journal of Sports Medicine)
Background: Tearing of the proximal hamstring tendon is a common injury in athletes for which surgical repair is being increasingly utilized. The described techniques for endoscopic repair employ a simple or mattress suture configuration. We hypothesize that the incorporation of a running modified whipstitch may allow for increased suture purchase and sturdier tendon fixation. Indications: Patients with partial tears, 2-tendon tears and >2 cm retraction, or 3-tendon tears refractory to conservative management are typically indicated for surgery. Technique Description: In the prone position, 2 portals are established in the gluteal crease. Neurologic structures such as the posterior femoral cutaneous nerve and the sciatic nerve are visualized. The ischium is decorticated, and a triple-loaded suture anchor is placed in the ischial tuberosity. Using a tissue penetrator and a suture-passing device, a modified whipstitch suture configuration is constructed to secure the torn tendons. Results: Overall, following endoscopic surgical repair, most patients demonstrate improvement in functional outcomes metrics and achievement of patient acceptable symptom state in >70% of cases. Return-to-sport rate between 77.3% and 95% has been described in the literature. Discussion/Conclusion: Open repair utilizes a running suture configuration, whereas endoscopic repair has traditionally been performed with simple or mattress constructs. A modified whipstitch, performed endoscopically, may provide the durability of open repair with decreased rates of perioperative complications associated with endoscopic repair. Further work comparing suture techniques and postoperative outcomes should be investigated. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.